Live VM migration techniques in cloud environment - A survey - Leelipushpam, P. Getzi Jeba; Sharmila, J. (2013 IEEE Conference on Information and Communication Technologies, 2013)
Cloud computing is a service where storage and computing resources can be accessed on subscription basis. Cloud computing is powered by the concept of virtualization technology. The virtual machines (VM) are hosted in servers so that user's requests are serviced in an optimal manner. The process of moving a running virtual machine or application between different physical machines without disconnecting the client or application is referred to as Live Migration. System resources memory, storage, process and Network resources like connectivity that are allocated to the virtual machine are transferred from the original host machine to the destination machine. Live Migration is performed for achieving Energy efficiency, Load Balancing and High availability of physical servers in Cloud Data center. This paper presents a detailed survey on Live Migration of Virtual machines in cloud environment.